Air Pollution in Metropolitan Perth and Cardiovascular and Respiratory Hospital Admissions - Hannelly, Toni Maree (Curtin University, 2017)
This two-stage study analysed historical and recent air quality data in metropolitan Perth. The first stage examined historical ambient air quality and hospital admission data over a 10-year period (2001-2010) to determine whether levels of pollutants in the Perth metropolitan airshed contributed to the number of unscheduled hospital admissions for cardiovascular and respiratory illness. The second stage consisted of monitoring ambient air quality, specifically particulate matter, and collecting samples to determine the size-specific metal composition.